Análise dos mecanismos de combate à vulnerabilidade social na universidade federal rural do semi-árido - Menezes, Leia Mara de (Universidade Federal Rural do Semi-Árido, 2019)
This study deals with the theme of social vulnerability and its traits in higher education. The notion of social vulnerability adopted is the one proposed by Kaztman (2000). According to this author, social vulnerability can be understood as the inability of a person or household to access opportunities that are available in various socioeconomic areas to improve their welfare situation or prevent their deterioration. Based on this, the research aims to understand how the public university contributes to avoid social vulnerability through the use of management mechanisms. The specific objectives are: a) To identify resources that, in light of UFERSA's official documents, prevent social vulnerability. b) Discuss, from the date collected, to what extent dropout and retention are traits of the effectiveness of mechanisms that prevent social vulnerability in the university. The research was conducted at the Rural Federal University of Semi-Arid (UFERSA), and the choice for this locus of study is justified by the significant expansion that the institution has experienced in recent years, since with the expansion of access, the problem of students' permanence. It was decided to develop the work in a public university because it understands that this is an integral part of the state, provider of social assets and opportunity structures. For the research, which has a qualitative nature and is classified as exploratory, we used the literature review through books, scientific articles and legislation. During the documentary and field investigation phase, in order to achieve the proposed objectives, several official documents were consulted and data were collected regarding the university mechanisms that reduce social vulnerability, contributing to the student's permanence in the institution. As a result, it was found that UFERSA has mechanisms that help students to address the social vulnerability, such as the Student Housing, the University Restaurant; the Institutional Permanence Program (IPP); the stages; the Monitoring Program and the Academic Mobility Program. These structures of opportunity are effective as they provide access to financial, human and social assets that enable students to remain in the university environment. However, although effective, the analysis showed that their access by students is still quite limited
Keywords: Vulnerabilidade social; Universidade; Mecanismos de gestão; Administração pública; Social vulnerability; University; Management mechanisms; Public administration; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA